ANALISIS STRUKTUR GEDUNG DPRD KOTA BUKITTINGGI MENGGUNAKAN SNI BETON BERTULANG 2847:2019 DAN SNI GEMPA 1726:2019 - Medriosa, Hamdeni; Wirahadi Kusuma Wau, Antonius (Jurnal Teknologi dan Vokasi, 2023)
Structural design is an important element in the construction of a building in order to produce a building that is strong, safe and economical. The overall structure of the building consists of two parts, namely the upper structure in the form of floors, beams, columns, walls and roof while the lower structure is in the form of a foundation. The DPRD building for the city of Bukit Tinggi will be analyzed using the Special Moment Resisting Frame Structure (SRPMK) system based on the procedure for calculating reinforced concrete structures using (SNI 2847-2019). Earthquake load analysis uses the spectrum response method based on earthquake resistance planning procedures for building and non-building structures using (SNI 1726-2019). Analysis of minimum design loads and related criteria for buildings and other structures using (SNI 1726-2020). Modeling in this study uses software based on 3D finite elements using SAP2000. The results of this study explain that the modeling meets the requirements for SNI-1726-2019 earthquake design and SNI 03-2847-2019 reinforced concrete design.